A importância da informação contábil no processo de tomada de decisão nas instituições religiosas da Diocese de Montenegro/RS - Rockenbach, Gabriele (My University, 2019)
This monograph focuses on: The Importance of Accounting Information in the Decision-Making Process in the Religious Institutions of the Diocese of Montenegro - RS. It is visible the growth of third sector entities that play an important role in the Brazilian economy because they do not have as their main objective, profit, but the human being. Third Sector organizations aim at developing their activities to generate benefits for society. Religious institutions, in bringing about social change, also have the characteristics of third sector entities. With the purpose of advising the managers of the institutions, the accounting comes as a support, since the information produced, if used in a timely manner, will help in the decision making. Thus, the objective of this paper is to analyze the use of accounting records in the decision-making process by the managers of the parishes that make up the Diocese. This research is classified as descriptive and qualitative, and also this paper presents a case study on the functionality and use of accounting of a Religious Organization belonging to the Catholic, Apostolic and Roman Church, called Mitra Diocesana of Montenegro, which operates in thirty-one. two municipalities in the region, which constitute the diocese. Non-profit entity that aims to evangelize, value and grow human beings. Although it is an immune organization, it has an obligation to keep bookkeeping. Therefore, with the evidence presented throughout this monograph, this work certainly contributes to the management of goods placed at the service of evangelization, the end activity of religious institutions.
Esta monografia enfoca: A Importância da Informação Contábil no Processo de Tomada de Decisão nas Instituições Religiosas da Diocese de Montenegro ?RS. É visível o crescimento das entidades de terceiro setor que exercem um importante papel na economia brasileira por não terem como objetivo principal, o lucro, mas sim o ser humano. As organizações do Terceiro Setor visam mediante o desenvolvimento das suas atividades gerar benefícios para a sociedade. As instituições religiosas, ao provocarem mudanças sociais, também possuem as características das entidades do terceiro setor. Com o fim de assessorar os gestores das instituições, a contabilidade surge como meio de apoio, uma vez que as informações produzidas, se utilizadas de forma oportuna, auxiliarão na tomada de decisão. Sendo assim, o objetivo deste trabalho é analisar a utilização dos registros contábeis no processo de tomada de decisão por parte dos gestores das paróquias que compõem a Diocese. Esta pesquisa se classifica como descritiva e qualitativa, e também este trabalho apresenta um estudo de caso sobre a funcionalidade e a utilização da contabilidade de uma Organização Religiosa pertencente à Igreja Católica, Apostólica e Romana, denominada Mitra Diocesana de Montenegro, que atua em trinta e dois municípios da região, os quais constituem a Diocese. Entidade sem fins lucrativos que tem como objetivo a evangelização, a valorização e o crescimento do ser humano. Embora seja uma organização imune, tem obrigação de manter escrituração contábil. Portanto, com as evidências apresentadas ao longo desta monografia certamente este trabalho contribui na gestão dos bens colocados a serviço da evangelização, atividade fim das instituições religiosas.(sic)
Keywords: Contabilidade gerencial; Associações sem fins lucrativos